Discharge against Medical Advice in Pediatric Intensive Care Unit and Subsequent Events - Dadang Hudaya Somasetia; Susanto Isman; Nathania Wonoputri (International Journal of Integrated Health Sciences, 2015)
Objective: The occurence of discharge against medical advice (DAMA) has impacted globally. Decisions of DAMA in pediatric patients are not made by the patients, but pose life-threatening consequences, especially for children treated in Pediatrics Intensive Care Unit (PICU). The present study aimed to identify the occurence of DAMA and subsequent events to the DAMA patients after treated in PICU of Dr. Hasan Sadikin General Hospital Bandung, Indonesia.Methods: A retrospective study from medical records of DAMA patients from PICU of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, between April 2011 and April 2012. Results: A total of 195 children aged 1–5 years were admitted. Of this number, 12 (6.2%) were DAMA. Financial problems were the most common reason for DAMA, followed by parents’ perception about their child’s terminal condition. The majority of parents were laborer. Last parents’ education level was mostly elementary school. Most patients who DAMA from PICU died in less than 24 hours.Conclusions: A considerable number of DAMA was found in our PICU. High mortality occured after patients asked for DAMA from PICU.Keywords: Discharge against medical advice (DAMA), pediatric, pediatrics intensive care unit (PICU) DOI: 10.15850/ijihs.v3n1.400